The case for exploring the usage of employee wellness programs for pediatric asthma control. (2nd January 2019) - Jassal, Mandeep S.; Butz, Arlene
ABSTRACT: The multiple socioecological determinants of asthma mandate that pediatricians develop a treatment strategy beyond the practice-based setting. To expand to a more impactful community-based role, pediatricians must look to form partnerships with groups that are capable of promoting social and environmental change. Traditionally, these groups have included schools, governmental agencies, and child care establishments. One group that is not actively being availed of are employers who have shown success in improving adult-based outcomes through wellness programs. Employers are stakeholders in pediatric asthma care through its impact on reduced worker productivity and higher health insurance premiums. An employer's focus on pediatric asthma will be a collective win for the employer and employee. The article herein describes the rationale for the focus of employers on pediatric asthma care and potential incorporation within employer-based wellness strategies.